HUBUNGAN TINGKAT EKONOMI KELUARGA DAN PENGETAHUAN IBU TENTANG STATUS GIZI BALITA DENGAN STATUS GIZI BALITA DI POSYANDU SUBUR KELURAHAN PULAI ANAK AIR WILAYAH KERJA PUSKESMAS NILAM SARI BUKITTINGGI TAHUN 2016 - Susanti, Evi; Wulandari, Shinta (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Puberty in our lives usually begins at the age of 8 to 10 years and ending approximately at the age of 15 to 16 years, the onset of puberty in women is characterized by rapid physical growth, menarche, psychological changes and the emergence of secondary sex characteristics. Many factors internal and external factors related to the occurrence of menarche. Internal factors such as the status of maternal menarche (genetic), and external factors such as social, economic, nutrition, exposure to mass media and lifestyle. Thus the purpose of this study was to determine the factors associated with age at menarche VIII grade student MTsN type 1 Bukitinggi 2016. This study used descriptive qualitative approach is too in-depth interviews with 5 participants (students of class VIII). This research was conducted on 2 September 2016. The results of interviews conducted in participants gained five themes in this study are 1) Knowledge of menarche symptoms, 2) Genetic Influence, 3) Nutritional Status, 4) Habits Everyday, 5). Watching Tv activity. Suggestions For the results of this study can be used as reference materials and reference for other researchers associated with the research and increase knowledge and information to the participants about menarche.